1989
DOI: 10.1128/mcb.9.1.349
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinant of the species-specific transcription of the mouse rRNA gene promoter.

Abstract: Mammalian ribosomal DNA (rDNA) transcription has a certain species specificity such that, both in vivo and in vitro, human rDNA cannot be transcribed by mouse machinery and vice versa. This is due to a species-dependent transcription factor, TFID (Y. Mishima, I. Financsek, R. Kominami, and M. Muramatsu, Nucleic Acids Res. 10:6659-6670, 1982). On the basis of the information obtained from 5' and 3' substitution mutants, we prepared a chimeric gene in which the mouse sequence from positions -32 to -14 was insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…First, we demonstrate that both hSL1 and mSL1 exhibit species-specific DNA recognition properties in the presence or absence of UBF. Moreover, the sequences that mSL1 protects from DNase I cleavage are very similar to the sequences defined previously as SSEs by use of human and mouse promoter chimeras (Safrany et al 1989). In contrast, UBF from both species shows interchangeable DNA binding and transcriptional activation properties.…”
Section: Role Of the Ubf-sl1 Complex In Promoter Recognitionmentioning
confidence: 53%
See 3 more Smart Citations
“…First, we demonstrate that both hSL1 and mSL1 exhibit species-specific DNA recognition properties in the presence or absence of UBF. Moreover, the sequences that mSL1 protects from DNase I cleavage are very similar to the sequences defined previously as SSEs by use of human and mouse promoter chimeras (Safrany et al 1989). In contrast, UBF from both species shows interchangeable DNA binding and transcriptional activation properties.…”
Section: Role Of the Ubf-sl1 Complex In Promoter Recognitionmentioning
confidence: 53%
“…DNase I footprinting studies of TF-ID, an activity identified in both mouse and human cells, shows very similar footprinting patterns to those observed with reactions containing a combination of UBF and SL1 at their cognate rRNA promoters (Safrany et al 1989). In addition, like SL1, TF-ID can reprogram heterologous transcription extracts .…”
Section: Role Of the Ubf-sl1 Complex In Promoter Recognitionmentioning
confidence: 83%
See 2 more Smart Citations
“…SL1 is analogous to the TFIID and TFIIIB factors in the Pol II and Pol III transcription systems and consists of TATA-binding protein (TBP), plus three distinct TBPassociated factors (TAFs) essential to reconstitute Pol I transcription (Comai et al 1992;Eberhard et al 1993;Hernandez 1993). In the presence of UBF, the SL1 complex binds the DNA template and extends the DNase I footprint to include the species-specific element (SSE) (Bell et al 1988;Safrany et al 1989).…”
mentioning
confidence: 99%